If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-3=9x+32
We move all terms to the left:
4x-3-(9x+32)=0
We get rid of parentheses
4x-9x-32-3=0
We add all the numbers together, and all the variables
-5x-35=0
We move all terms containing x to the left, all other terms to the right
-5x=35
x=35/-5
x=-7
| −10(x−4)2=−160 | | 62+98+6x=270 | | (3*4)+4y=8 | | 30+15x=36+12x | | -7(4-x)=-3x+-9 | | 207-v=88 | | 4x-3=9x=32 | | 6(4-x)=-3x+7 | | 11q−9q=18 | | 26=2p-32 | | p=10.5=18.32 | | (10x-70)/(50x)=0 | | 3+4•x=39 | | 9^u=81 | | 9(4-x)=-3x+-9 | | 2a+4a+6a=36 | | m+5m=6 | | -5/2(x-9/4=5/8 | | -7o=(5-3o) | | 9(p-88)=45 | | |x/5|-10=-9 | | 54=0.9•r | | (3x)(x-7)=(4x-7) | | 5,4(y+3)=4(y+3) | | 1/2n-1=-13/8 | | m/7*3=0 | | 9(4-x)=-3x+-1 | | 15–2x=30–5x | | 9(3z+4)=0= | | 7g=–9+10g | | 9(4-x)=-3x+71 | | 7(2-x)=9=2 |